Amyloid-induced mitochondrial network disruption in neurons monitored by STED super-resolution imaging - Golovynska, Iuliia; Chen, Qinglin; Stepanov, Yurii V.; Lin, Danying; Qu, Junle (Frontiers in Cell and Developmental Biology, 2025)
IntroductionDisruptions in mitochondrial metabolism are accompanied by morphological changes in mitochondrial network caused by amyloid-beta (Aβ). In the study, mitochondrial network analysis is performed using stimulated emission depletion (STED) super-resolution fluorescence microscopy to examine alterations in neurons exposed to Aβ in vitro.MethodsA detailed analysis of mitochondrial network in healthy neurons and those exposed to Aβ is performed using STED compared to conventional laser-scanning confocal fluorescence microscopy. The functional analysis is applied to mitochondrial volume, surface area, branch length, diameter, junctions, and endpoints. Neurons incubated with or without Aβ were also stained with fluorescent mitochondrial function indicators.ResultsIn neurons exposed to Aβ, the number of mitochondria increases by 2.6 times, while their total volume decreases by 2.2 times. As a result, the volume and surface area per mitochondrion decrease by 6-fold and 4-fold, respectively. Increases in sphericity, branch diameter, and donut-like structures are observed. The total mitochondrial length is 3.7-fold reduced, while the number of branches is 2.5-fold decreased, and the branch count is 7.5-fold reduced. Additional measurements reveal decreased mitochondrial membrane potential, increased reactive oxygen species generation, and reduced cell viability. This may indicate that Aβ exposure causes significant oxidative stress, mitochondrial integrity loss, and ultimately neuronal death.ConclusionAβ induces mitochondrial fragmentation, thickening, increased sphericity, and deformation of mitochondrial matrix in neurons. The results provide insights into the impact of Aβ on neurons and show the aptitude of the high-resolution STED microscopy diagnostic tool for neurodegenerative diseases.